Perfil dos empreendedores e caracterização dos empreendimentos do centro comercial de Viçosa-RN - Dantas, Leonardo Henrique de Macedo (Universidade Federal Rural do Semi-Árido, 2018)
The present study had as a principle the characterization of the profiles of the entrepreneurs of the city of Viçosa in Rio Grande do Norte, in order to understand the main problems that most affect their development in the economic and so social. It has been identified that it has a low rate of development, a significant lack of innovative entrepreneurship, new ideals, and fragile infrastructure. With regard to the profile of the entrepreneur, we addressed issues involving the predominant age range in the market, type of enterprise, whether legalized or not, as well as the distribution by gender, educational level, among other characteristics. Through the results obtained through the field research conducted at the commercial center of the city of Viçosa-RN, it was observed that the predominant age group is between the ages of 21 to 30 years, the number of entrepreneurs is greater for the male gender. Regarding schooling, it was observed that most entrepreneurs have completed high school. Among the activities carried out in said city, the services sector prevails, most of the enterprises are micro-enterprises.
Monografia
Keywords: Empreendedorismo; Desenvolvimento; Problemático; Entrepreneurship; Development; Problems; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA